Role of the Bridge in Photoinduced Electron Transfer in Porphyrin–Fullerene Dyads. Issue 15 (3rd March 2015) - Pelado, Beatriz; Abou‐Chahine, Fawzi; Calbo, Joaquín; Caballero, Rubén; de la Cruz, Pilar; Junquera‐Hernández, José M.; Ortí, Enrique; Tkachenko, Nikolai V.; Langa, Fernando
Abstract The role of π‐conjugated molecular bridges in through‐space and through‐bond electron transfer is studied by comparing two porphyrin–fullerene donor–acceptor (D–A) dyads. One dyad, ZnP–Ph–C60 (ZnP=zinc porphyrin), incorporates a phenyl bridge between D and A and behaves very similarly to analogous dyads studied previously. The second dyad, ZnP–EDOTV–C60, introduces an additional 3, 4‐ethylenedioxythienylvinylene (EDOTV) unit into the conjugated bridge, which increases the distance between D and A, but, at the same time, provides increased electronic communication between them. Two essential outcomes that result from the introduction of the EDOTV unit in the bridge are as follows: 1) faster charge recombination, which indicates enhanced electronic coupling between the charge‐separated and ground electronic states; and 2) the disappearance of the intramolecular exciplex, which mediates photoinduced charge separation in the ZnP–Ph–C60 dyad. The latter can be interpreted as a gradual decrease in electronic coupling between locally excited singlet states of D and A when introducing the EDOTV unit into the D–A bridge.